The attitudes of nurses towards internship in the Republic of Croatia - Vuković, Ivica-Tvrtko (Array, 2019)
The internship in health care is regulated by the Rules and Regulations on Internship of Health Care Providers. One of the measures of the Croatian Institute for promoting employment of interns in health care is “Professional Training for Work Without Establishing an Employment Relationship”. The aim of this research is to determine the attitudes towards internship and to determine whether there is a statistically significant difference between the attitudes of currently employed nurses and those currently doing an internship. The research was conducted through the Internet, using an anonymous questionnaire containing 10 questions, out of which 8 were closed-ended and 2 open-ended questions. A total of 306 respondents were interviewed, of whom 232 were nurses and 49 nursing interns. When asked whether internship is necessary in health care, 98.4% of the respondents answered positively, with the majority of interns (75.3%) considering that there is a need for changes in internship. The results of the chi-square test suggest that there are statistically significant differences in the attitudes of employed respondents and interns in the answers to 5 questions. The interns rated their knowledge of internship worse than healthcare workers and workers in other systems. Interns associate internship with exploitation, while employed nurses mention that it reminds them of training for independent work. Most healthcare professionals would like someone close to them to have the right/obligation to do internship. By analyzing the results of the attitudes towards internship, a statistically significant difference between currently employed nurses and nursing interns was established. It is felt that youth training should be the responsibility of the employers who should provide adequate education and continuous monitoring of new workers.